Homophily Groups, Social Capital and Community Development in Cameroon - Forje, Lema Catherine (Advances in Social Sciences Research Journal, 2021)
Social groups have contributed enormously in community development in Cameroon. Such contributions have very often been overlooked by policy makers, as such; is not included in policy formation. Social capital generated by groups has been discussed at length in the literature, but its effects on the society remain unclear, thus often only associated with poverty. Such association discourages creative endeavours as well as distorts its meaning and functioning. It also misleads future studies and distort their information searching path. This study discusses how homophily groups in Cameroon get funds from members, the diasporas and well wishers and use to provide services to the community. Some of the projects provided by these social groups include: school buildings, hospitals, water supply tanks; church buildings and equipments. They also provide individual security in the form of supporting vigilantic groups that help maintain law, order and peace in the community at large. The paper discusses the bases of their group formation which is the core of group sustainability. Data was collected from two large homophily groups, one ethnicity and one alumnae base with an average of one hundred and twenty five members per group in one region in Cameroon, and twenty five related Cameroonian in the diasporas. The result shows that the homophily groups are very devoted and committed in carrying out developmental projects in their various communities. The implication is that this study will encourage policy makers to recognise the activities of such groups which could motivate the emergence of others to imitate the approach to the overall communities. The recommendation is that they need to invest in money generating activities to enable them achieve their objectives without the strain of constantly dipping into their personal budget and depending on external sources for sustainability. The society needs to be educated to know the contributions of groups in the community.